1998
DOI: 10.1007/s002449900341
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Extraction Procedure on Ion Concentrations in Sediment Pore Water

Abstract: Sediment pore water has the potential to yield important information on sediment quality, but the influence of isolation procedures on the chemistry and toxicity are not completely known and consensus on methods used for the isolation from sediment has not been reached. To provide additional insight into the influence of collection procedures on pore water chemistry, anion (filtered only) and cation concentrations were measured in filtered and unfiltered pore water isolated from four sediments using three diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 35 publications
2
33
0
1
Order By: Relevance
“…At an ionic strength of 0.01, HA could not be dissolved, hence the solubility enhancement method cannot be used. The constituents of the soil pore water (ionic strength 0.01) were taken from Winger et al [20] with some modification. Soil pore water was found to be rich in alkalinity (as bicarbonate); however, due to the difficulty in manipulating pH, sodium chloride was used instead of bicarbonate.…”
Section: Solubility Enhancement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At an ionic strength of 0.01, HA could not be dissolved, hence the solubility enhancement method cannot be used. The constituents of the soil pore water (ionic strength 0.01) were taken from Winger et al [20] with some modification. Soil pore water was found to be rich in alkalinity (as bicarbonate); however, due to the difficulty in manipulating pH, sodium chloride was used instead of bicarbonate.…”
Section: Solubility Enhancement Methodsmentioning
confidence: 99%
“…In the present study, sorption of endosulphan sulphate in soil humic and fulvic acid was investigated at an ionic strength 0.001, which is the typical ionic strength of surface run-off, and at 0.01, which is the typical ionic strength of the soil pore water [20]. The study was first to describe the sorption of endosulphan sulphate in soil organic matters.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor and Shiller (1995) point out that preloading the filter (e.g., that is, pre-rinsing the filter in order to remove contaminants) can reduce the filter's effective pore size which could also affect the soluble/ particulate percentage value. Winger et al (1998) found that concentrations of most cations in filtered pore water were slightly lower when compared to those of the same water unfiltered. They also found that the loss of trace metals (lead and copper, among others) was especially significant after filtering with a 0.45-μm nylon syringe filter.…”
Section: Introductionmentioning
confidence: 91%
“…Several methods have been employed to extract the sediment pore-water, including centrifugation (Ankley and Schubauer-Berigan, 1994;Carr and Chapman, 1995;Ozretich and Schults, 1998;Doig and Liber, 2000;Kelln et al, 2001), pressurization (Carr et al, 1989;Chapman, 1992, 1995;Kelln et al, 2001), suction (Bufflap and Allen, 1995;Carr and Chapman, 1995;Carr et al, 1996;Winger et al, 1998), and equilibration methods using dialysis membranes or fritted glass samplers (Jacobs, 2002;Lewandowski et al, 2002;Williamson et al, 2002). With the latter two methods (suction and dyalisis), the extraction of pore-water can be accomplished in place (Bufflap and Allen, 1995;Angelidis, 1997;Doe et al, 2003).…”
Section: Introductionmentioning
confidence: 95%